Urban design and the British urban renaissance [ - Punter, John (Routledge, 2010)
An insightful exploration of the strengths, weaknesses and implications of New Labour's urban renaissance agenda, experts in urban design and planning critically review the development and application of the strategy in Britain's largest cities.